The Role of Allergy Testing in Eosinophilic Esophagitis - Anyane-Yeboa, Adjoa (Gastroenterol Hepatol (N Y), 2018)
Eosinophilic esophagitis (EoE) is defined as a chronic, immune/antigen-mediated esophageal disease that can lead to symptoms of esophageal dysfunction. This disease is seen in both children and adults. Approximately 70% of patients with EoE have food antigen sensitization or other atopic conditions, suggesting an allergic etiology in the pathogenesis of the disease. The role of allergy testing to identify foods that lead to EoE is unclear. Three types of allergy tests currently exist: skin prick testing, atopy patch testing, and immunoassays for serum food-specific immunoglobulin E. It is important for gastroenterologists to work in conjunction with allergist colleagues in the care of patients with EoE, particularly in the management of comorbid atopic conditions.